Phytochemical Screening of Secondary Metabolites of 96% Ethanol Extract of Coriander Seeds (Coriandrum Sativum L.) - Ni Putu Oka Mahayani*; Bagus Komang Satriyasa; I Wayan Sumardika (Riwayat: Educational Journal of History and Humanities, 2023)
Coriander seeds are spices that are generally used by Indonesian people not only as a food ingredient, but also as a medicinal ingredient. The purpose of this study was to determine the content of secondary metabolites in coriander seeds ( Coriandrum sativum L.). This study used the maceration extraction method with 96% ethanol as a solvent and then continued with phytochemical screening. From the results of the phytochemical screening of 96% ethanol extract of coriander seeds ( Coriandrum Sativum L.), it was found that the extract contained phenolic compounds, flavonoids, tannins, saponins, triterpenoids and steroids, and did not contain alkaloids .